Associated factors of pregnancy spacing among women of reproductive age Group in South of Iran: cross-sectional study - Tania Dehesh; Elaheh Salarpour; Neda Malekmohammadi; Sepideh Arjomand Kermani (BMC, 2020)
Abstract Background Optimal pregnancy spacing is an important incidence in reproductive women's health. Short or long pregnancy spacing leads to the greatest health, social and economic problems such as increase in maternal and infant mortality and morbidity, and adverse pregnancy outcomes. The aim of this study is to assess the mean of pregnancy spacing and associated factors of pregnancy spacing among women of reproductive age group with recurrent event analysis. Methods The fertility history of 1350 women aged 15-49 years was collected in this cross-sectional study. The women were selected through multistage random sampling method from a list of clinics in 2018. Some predictors were collected from their records and others were collected by face-to-face interview. The recurrent event survival analysis was used to explore the effect of predictors on pregnancy spacing. The R software program was used for analysis. Results There were nine predictors that had significant effect on pregnancy spacing. These predictors included the age of mother at marriage, mother's BMI, contraception use, breast feeding duration of the previous child, the education level of husband, the sex preference of the mother, presence of abortion or stillbirth in the preceding pregnancies, income sufficiency, and mother's awareness of optimum pregnancy interval. The most influential predictors; contraception use (HR = 2.34, 95%CI = 1.23 to 2.76, P < 0.001) and income sufficiency (HR = 2.046, 95%CI = 1.61 to 3.02, P = 0.018) lead to longer and son preference of mother (HR = 2.231, 95%CI = 1.24 to 2.81, P = 0.023) lead to shorter pregnancy spacing. Conclusion The up to date contraception tool should be at hand for couples to manage their pregnancy intervals. The unfavorable economic situation of a family leads to long pregnancy spacing. Despite the relative equality of the status of girls and boys in today's societies, the desire to have a son child is still an important factor in shorter pregnancy spacing. The benefit of optimal pregnancy spacing should be more announced.